Directional selection reduces developmental canalization against genetic and environmental perturbations in Drosophila wings. (1st August 2018) - Groth, Benjamin R.; Huang, Yuheng; Monette, Matthew J.; Pool, John E.
Abstract: Natural selection may enhance or weaken the robustness of phenotypes against genetic or environmental perturbations. However, important aspects of the relationship between adaptive evolution and canalization remain unclear. Recent work showed that the evolution of larger wing size in a high altitude natural population of Drosophila melanogaster was accompanied by decanalized wing development–‐specifically a loss of robustness to genetic perturbation. But this study did not address environmental robustness, and it compared populations that may have numerous biological differences. Here, we perform artificial selection on this same trait in D. melanogaster (larger wing length) and directly test whether this directional selection resulted in decanalization. We find that in general, size‐selected replicates show greater frequencies of wing defects than control replicates both after mutagenesis (genetic perturbation) and when subjected to high temperature stress (environmental perturbation), although the increase in defect frequency varies importantly among replicates. These results support the hypothesis that directional selection may result in the loss of both genetic and environmental robustness–offering a rare window into the relationship between adaptation and canalization.